Crossing the waters : following Jesus through the storms, the fish, the doubt, and the seas - Fields, Leslie Leyland, 1957- (Colorado Springs, CO : NavPress, 2016)
The gospels are dramatic, wild, and wet, set in a rich maritime culture on the shores of the Sea of Galilee. Jesus' first disciples were ragtag fishermen, and Jesus' messages and miracles teem with water, fish, fishermen, net-breaking catches, sea crossings, boat-sinking storms, and even a walk on water. Because this world is foreign and distant to us, we've missed much about the disciples' experiences and about following Jesus until now. Leslie Leyland Fields, a well-known writer, respected biblical exegete, and longtime Alaskan fisherwoman crosses the waters of time and culture to take us out on the Sea of Galilee, through a rugged season of commercial fishing with her family in Alaska, and through the waters of the New Testament. You'll be swept up in a fresh experience of the gospels, traveling with the fishermen disciples from Jesus' baptism to the final miraculous catch of fish, and also experiencing Leslie's own efforts to follow Christ out on her own Alaskan sea. In a time when so many are "unfollowing" Jesus and leaving the Church, Crossing the Waters delivers a fresh encounter with Jesus and explores what it means to "come, follow me."
The gathering of the waters -- Under the waters -- Calling out of water -- The catch of catches -- A fish or a snake? -- Rocking the boat -- Mending the world -- Storming the peace -- Filling the hungry -- Over the waters -- Unfollowing Jesus -- The final catch.
Includes bibliographical references.
Keywords: Fishing -- Religious aspects -- Christianity; Storms -- Miscellanea; Seafaring life -- Religious aspects